Acute Response of Well-Trained Sprinters to a 100-m Race: Higher Sprinting Velocity Achieved With Increased Step Rate Compared With Speed Training. Issue 3 (March 2016) - Otsuka, Mitsuo; Kawahara, Taisuke; Isaka, Tadao
Abstract : Abstract: Otsuka, M, Kawahara, T, and Isaka, T. Acute response of well-trained sprinters to a 100-m race: higher sprinting velocity achieved with increased step rate compared with speed training. J Strength Cond Res 30(3): 635–642, 2016—This study aimed to clarify the contribution of differences in step length and step rate to sprinting velocity in an athletic race compared with speed training. Nineteen well-trained male and female sprinters volunteered to participate in this study. Sprinting motions were recorded for each sprinter during both 100-m races and speed training (60-, 80-, and 100-m dash from a block start) for 14 days before the race. Repeated-measures analysis of covariance was used to compare the step characteristics and sprinting velocity between race and speed training, adjusted for covariates including race-training differences in the coefficients of restitution of the all-weather track, wind speed, air temperature, and sex. The average sprinting velocity to the 50-m mark was significantly greater in the race than in speed training (8.26 ± 0.22 m·s −1 vs. 8.00 ± 0.70 m·s −1, p < 0.01). Although no significant difference was seen in the average step length to the 50-m mark between the race and speed training (1.81 ± 0.09 m vs. 1.80 ± 0.09 m, p = 0.065), the average step rate was significantly greater in the race than in speed training (4.56 ± 0.17 Hz vs. 4.46 ± 0.13 Hz, p < 0.01). These findings suggest that sprinters achieve higher sprinting velocity and can run with higher exercise intensity and more rapid motion during a race than during speed training, even if speed training was performed at perceived high intensity.